Processes Of Learning And Teaching Multiple Subjects In Higher Education Institutions - Qutbiddinov Xikmatillo Qudratilli o‘g‘li (Peerian Journals Publishing, 2024)
In our country In HEIs lots of shoe topics are taught in the process there are problems and practical affairs about data given
Keywords: Kopyaks; student; High education institution; drawing